Experiences on "Covid-19 pandemic" in urban design course education - Tapkı, Sinem (My University, 2023)
Today, it is observed that the current architectural planning of public spaces, squares, streets, parks and buildings can disappear and change over time, as the Covid-19 pandemic is easily effective on people and settlements on a global and regional scale. The aim of the study, which takes these changes into consideration, is to open the solution suggestions to the discussion in the process of simultaneously exploring the grounded problems while sharing the experiences of the pandemic process within the education of urban design course students. A study was carried out that was interpreted with participant interaction. Current pandemic experiences were utilized within the process of stratifying the structured opinions. The constructivist grounded theory of qualitative research pattern forms the skeleton of this solution-seeking study. Considering the interview answers made with the students, it has been observed that they gave many answers, as well as suggestions for solutions, that the pandemic will experience changes, especially in urban and public spaces and residences. It is noteworthy that the city and the surrounding areas in which they live are uniform places that do not respond to the requests of the users during the pandemic process and that the students realize the inadequacies of these uniform spaces.
Keywords: Covid-19 pandemic; Design; Constructivist grounded theory